1885 Fla. Laws 61 - (:unkn) unknown (My University, 1885)
Fla. Act of Feb. 12, ch. 3620: Prohibited the concealed carrying of any arms, dirk, pistol, or other arm or weapon is guilty of a misdemeanor. Fines not exceeding one hundred dollars or six months imprisonment.
Keywords: CARRY - CONCEALED